Carbidopa and ZnCarbidopa Induce Reductive Stress in MDA‐MB‐231 Cells - Actis Dato, Agustín Bruno (2024)
The redox imbalance, caused by depletion or generation of reactive oxygen species (ROS), is a key mechanism by which metal complexes exert anticancer effects. Carbidopa has shown the ability to inhibit the MDA-MB-231 cell line, a highly aggressive triple-negative human breast adenocarcinoma, by inducing reductive stress. The metal complex of carbidopa with zinc (ZnCarbi) was designed to modify carbidopa´s structure and exhibited increased cytotoxicity against MDA-MB-231 cells. Interestingly, ZnCarbi selectively targets certain cancer cells, showing no impact on the viability of normal HEK293 (human embryonic kidney) cells or other cancer cell lines like A549 (human lung adenocarcinoma), LM3 (murine breast adenocarcinoma), or HCT116 (human colon cancer). Treatment with carbidopa and ZnCarbi induces reductive stress, decreases ROS levels, increases the GSH/GSSG ratio, and protects cells from H2O2-induced death. Both compounds also cause mitochondrial damage, leading to cell death, and exhibit antimetastatic effects by inhibiting cell migration and invasion of MDA-MB-231 cells. Interaction studies with bovine serum albumin showed moderate binding through hydrophobic association. Overall, ZnCarbi demonstrates enhanced anticancer properties compared to carbidopa alone, highlighting its potential as an anticancer and antimetastatic compound.